A Luminescent Mixed-Lanthanide Metal–Organic Framework Thermometer - Cui, Yuanjing; Xu, Hui; Yue, Yanfeng; Guo, Zhiyong; Yu, Jiancan; Chen, Zhenxia; Gao, Junkuo; Yang, Yu; Qian, Guodong; Chen, Banglin (Journal of the American Chemical Society, 2012)
A luminescent mixed lanthanide metal–organic framework approach has been realized to explore luminescent thermometers. The targeted self-referencing luminescent thermometer Eu 0.0069 Tb 0.9931 -DMBDC (DMBDC = 2, 5-dimethoxy-1, 4-benzenedicarboxylate) based on two emissions of Tb3+ at 545 nm and Eu3+ at 613 nm is not only more robust, reliable, and instantaneous but also has higher sensitivity than the parent MOF Tb-DMBDC based on one emission at a wide range from 10 to 300 K.